The Effect of Slow Deep Breathing Combined with Classical Music on Anxiety in Elderly Patients with Diabetes Mellitus: A Gerontological Nursing Case Study - Ni Putu Dita Wulandari; Ni Kadek Nita Lestari (Bali Medical and Wellness Journal, 2026)
Background: Diabetes mellitus (DM) is a chronic metabolic disorder characterized by persistent hyperglycemia. Global prevalence is rising, with an estimated 589 million cases in 2024 and a projected 853 million by 2050. Beyond physical health, DM often leads to psychological complications. Anxiety is 20% more prevalent in diabetic patients than in the general population, often resulting in poor glycemic control and a cycle of metabolic decline. Objectives: This study aims to analyze the effectiveness of combining slow deep breathing therapy with classical music as a non-pharmacological nursing intervention to manage anxiety in elderly patients with DM at Puskesmas Tabanan I. Method: A descriptive case study design was used, following the five-stage nursing process: assessment, diagnosis, planning, implementation, and evaluation. Three patients (aged 65–79 years) with a nursing diagnosis of Anxiety (SDKI D.0080) participated from December 5–7, 2025. The intervention consisted of a 60-minute session held once daily for three days. Anxiety levels were measured using the Indonesian Nursing Outcome Standard (SLKI L.09093). Results: After three sessions, all patients showed significant reductions in anxiety. Subjective findings included decreased worry and improved relaxation. Objective indicators showed reduced restlessness, less muscle tension, and the normalization of respiratory and heart rates. Additionally, patients reported higher confidence in managing their symptoms. Conclusion: Combining slow deep breathing with classical music is an effective, safe, and feasible non-pharmacological intervention for reducing anxiety in elderly diabetic patients. This approach is recommended as a complementary therapy in routine gerontological nursing care.